Why did Jesus, Moses, the Buddha, and Mohammed cross the road? : Christian identity in a multi-faith world - McLaren, Brian D., 1956- (New York : Jericho Books, 2012)
"Brian McLaren, one of the established leaders of the emerging church movement, invites interfaith dialogue, suggesting tolerance and respect between religions"--Provided by the publisher.
Includes bibliographical references.
Keywords: Christianity and other religions; Religions -- Relations; Identification (Religion); Pluralism -- religious aspects